MASALAH PSIKOSOSIAL PADA REMAJA DI KOTA BATAM TAHUN 2022 - Larasuci Arini; Setiadi Syarli; Aprilya Roza Werdani (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2023)
Adolescence will experience a period of transition or transition from childhood to maturity which is marked by physical, hormonal, psychological, social and psychosocial changes (Batubara, 2010). Adolescent psychosocial problems experienced by adolescents in the world, one of which is depression, shows the prevalence of depression in adolescents. The purpose of this study was to determine psychosocial problems in adolescents in the city of Batam. Respondents in this study totaled 51 people who conducted research on 7 -20 October 2022. The results obtained were from psychosocial problems. Students who experience psychosocial problems from 52 respondents are very small, namely 2 (2.2%). students who experience psychosocial externalization problems are 4 (4.3). Researchers hope that efforts to increase health promotion regarding sexual deviant behavior in various places are planned and sustainable with various competent parties.